Obesity: epidemics or crisis worldwide? (Italian Journal of Public Health, 2011)
The rapid increase in the level of obesity and overweight worldwide is recognized as a major health problem: obesity poses a major risk for serious diet-related diseases, including diabetes mellitus, cardiovascular disease, hypertension, stroke and cancer; therefore, it increases the risk of premature death. In particular, abdominal obesity - an increased amount of intra-abdominal fat - has been associated with a number of cardiovascular disease (CVD) risk factors, CVD and all-cause mortality [2]. Recent research demonstrated that high BMI values are associated with increased sympathetic activity, which results in decreased Heart Rate Variability (HRV).